Commentary on the Process of Gravity: Quantum Mechanics and Gravity Resonance Together - Ophir Flomenbom (Reports in Advances of Physical Sciences)
In a recent paper, “The process of gravity” (2022), we developed the theory to explain gravity, stating that gravity waves are created through a process involving quantum fluctuations of all the molecules of the celestial body. The local fluctuations of adjacent molecules interact, and this process on the macroscopic scale creates the gravitational waves: at steady state, these fluctuations are structured as layers of the onion, generating a force toward the body center of mass. Here, we further develop the theory microscopically, stating that all elementary particles vibrate at their own particular frequency of gravity, generating radiant energy, where their mass determines the radiant pulses strength. These quantum fluctuations are not photons; the fluctuations are connected to the mass. These might be defined as electromagnetic radiant phonons. Yet also, the frequency of gravity might reach 10[Formula: see text]–10[Formula: see text][Formula: see text]Hz, whereas these are not photons, the energy is not high at all. This description is valid also for black holes. There, gravity waves made of electromagnetic fluctuations engulf the singularity. As these fluctuations are connected to the mass, the waves can escape the black hole, within our layering description of gravity. An anti-gravity device should create a fluctuating magnetic field and electric field, in the adequate direction, at the required frequency and strength. The signal should annihilate the Earth’s gravitation waves. In this work, an anti-gravity device is designed and developed. It is based on a Tesla coil circuit of high voltage, and high frequency, connected to a coil on a rotating board, at a condensation temperature, yet all the ingredients are replaced and improved, including the rotation feature.